STRUKTUR MODAL DAN NILAI PERUSAHAAN : DIPENGARUHI OLEH UNIQUENESS, TANGIBILITY DAN FINANCIAL FLEXIBILITY - Delfi Agustiawan; Yulia Efni; Gusnardi Gusnardi (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
This study is aimed to examine the effect of uniquenss, tangibility and financial flexibility on capital structure and firm value. The population of this study is miscellaneous industry sector from 2015 - 2019. The sample of the study is all companies were selected by purposive sampling method. Based on the criteria, 33 companies were chosen as the samples of this study. This study used structural equation modeling with partial least square program to test whether the independent variables affect the dependent variables. The results of this study are found that (1) uniqueness has a negative and insignificant effect on capital structure, (2) tangibility has a positive and significant effect on capital structure, (3) financial flexibility has a positive and significant effect on capital structure, (4) uniqueness and tangibility have a positive and significant effect on firm value, whille financial flexibility has a negative and insignificant effect on firm value, (5) tangibility has a positive and significant effect on firm value through capital structure, while uniqueness dan financial flexibility have a negative and insignificant effect on firm value through capital structure, and (6) capital structure has a negative and significant effect on firm value.